The Effect of Social Support on the Empowerment Status and Alopecia-Related Quality of Life in Breast Cancer Patients: A Cross-Sectional Structural Equation Modeling Study - Bayrak, Nisa Yavuzer; Turan, Gulcan Bahcecioglu; Karabulutlu, Elanur Yilmaz (Wiley, 2026)
ObjectiveThis cross-sectional study was conducted to investigate the effect of social support on empowerment status and alopecia-related quality of life in breast cancer patients.MethodsThis study included 150 breast cancer patients who were admitted to the oncology outpatient clinic of a training and research hospital in Erzurum province, eastern Turkey, and met the inclusion criteria. Data were collected using the Descriptive Information Form, the Cancer Empowerment Scale, the Chemotherapy-Induced Alopecia Quality of Life Scale, and the Cancer Patient Social Support Scale. Structural equation modeling was used to examine the direct and indirect relationships among variables. This study was conducted in accordance with the STROBE guidelines.ResultsSocial support was found to positively affect empowerment status (beta = 0.960) and alopecia-related quality of life (beta = 0.335). Empowerment status had a positive and significant effect on alopecia-related quality of life (beta = 0.647). The indirect effect of social support on alopecia-related quality of life through empowerment status was positive and significant (beta = 0.622), and the total effect of social support on alopecia-related quality of life was also positive and significant (beta = 0.957). Social support explained 92% of the variance in empowerment status, and the overall model explained 94% of the variance in alopecia-related quality of life.ConclusionsSocial support positively influences both empowerment status and alopecia-related quality of life in breast cancer patients. In addition, social support improves alopecia-related quality of life indirectly by enhancing empowerment status. Strengthening social support mechanisms may therefore contribute to improved quality of life related to chemotherapy-induced alopecia in breast cancer patients.
Keywords: alopecia; breast cancer; cancer empowerment; nursing; social support